Productive performance of the single farrowing system for pigs - Daza, A.; Riopérez, J.; Ovejero, I.; de Alba, C. (Spanish Journal of Agricultural Research, 2005)
This paper reports two experiments, the aims of which were to contribute to the development of the single farrowing production system for pigs. The first reports the induction of oestrus in three groups of 70 Duroc gilts (167 days old, body weight 93.6 kg) via the injection of either 1000, 600 or 400 IU of pregnant mare serum gonadotrophin (PMSG) plus 500, 200 or again 200 IU of human chorionic gonadotrophin (hCG) respectively. No significant differences were observed among these treatments with respect to the percentage of gilts entering oestrus, their fertility or their prolificacy. The average number of piglets weaned per farrowed gilt was 5.61, 5.66 and 6.69 (P